Peran Kepercayaan Memediasi Hubungan Reputasi dan Intensi Pembelian di E-Commerce - Ratna Dewi Kusumawati; Lucia Ari Diyani (JURNAL ONLINE INSAN AKUNTAN, 2021)
This research is conducted to discover the mediation role of trust, especially trust to seller in e-commerce, to seller reputation and purchase intention relationship in e-commerce. Data in this research is collected using questionnaire. Data in this research is analyzed using Path Analysis and Sobel Test. Finding in this research shows that trust to seller is able to mediate the relationship between reputation and purchase intention in e-commerce. Other findings in this research is reputation variable affect purchase intention directly in statistic test, and reputation variable is affecting trust to seller variable and trust to seller variable significantly affect purchase intention variable. The finding is expected to contribute in providing new insights in accounting information systems research, especially related to e-commerce in Indonesia and are expected to provide reference contributions for future studies in the same field.